Assessing Biophysical and Physiological Profiles of Scalp Seborrheic Dermatitis in the Thai Population - Poonkiat Suchonwanit (2020)
© 2019 Poonkiat Suchonwanit et al. Background. Scalp seborrheic dermatitis (SD) is a common and chronic inflammatory skin disease which tends to recur over time. By measuring biophysical properties of the stratum corneum, many studies report abnormal biophysical profiles and their association in various dermatologic diseases. The aim of the study is to analyze the biophysical properties and skin barrier defects of scalp SD compared to healthy controls. Materials and Methods. This study is a cross-sectional study assessing the correlation of various biophysical and physiological profiles in scalp SD. Forty-two Thai participants with scalp SD were enrolled in the study and 40 healthy participants were also enrolled as the control group. Both SD and control group were subjected to a one-time biophysical and physiological properties' measurement of transepidermal water loss (TEWL), stratum corneum hydration (SCH), skin surface pH, skin surface lipid, and skin roughness. Results. The mean TEWL of lesional skin of SD cases were significantly higher than those of control group (P<0.05). Relating to high mean TEWL, the mean SCH was found to be significantly lower in SD cases (P<0.05). Skin surface lipid was also found to be significantly higher in SD group (P<0.05). However, there were no differences in skin surface pH (P=0.104) and roughness (P=0.308) between the two groups. Pairwise comparison of each subgroup found that moderate and severe SD demonstrated significantly higher mean skin surface lipid than that of control group (P<0.05). Conclusion. Scalp SD may be associated with seborrhea in Thai population. Monitoring of SCH, TEWL, and skin surface lipid could be helpful in assessing severity and evaluating the treatment outcome in patients with scalp SD.